Comparative Performance Analysis of VANET Routing Protocols under Dynamic Node Mobility - Fahrizal Djohar; Hafid Syaifuddin; Dharmawan Dharmawan (Universitas Khairun, 2025)
Vehicular Ad Hoc Networks (VANETs) face significant challenges in maintaining reliable communication due to high node mobility and frequent topology changes. This study evaluates the throughput performance of two routing protocols—one proactive and one reactive—under varying speed scenarios using the NS-3 simulator. Simulations were conducted in an area with node speeds set at 10 m/s (36 km/h) and 20 m/s (72 km/h). NetAnim was used to visualize node movement and routing behavior. The results show that the reactive protocol outperforms the proactive protocol in high-mobility scenarios by maintaining higher throughput and reducing routing overhead. These findings highlight the importance of selecting routing protocols that adapt effectively to different mobility conditions in VANETs, contributing to the design of more efficient vehicular communication systems.